Food and beverage marketing in primary and secondary schools in Canada - Potvin Kent, Monique; Velazquez, Cayley E; Pauzé, Elise; Cheng-Boivin, Olivia; Berfeld, Noami (Université d'Ottawa | University of Ottawa, 2019)
Abstract Background Unhealthy food marketing is considered a contributor to childhood obesity. In Canada, food marketing in schools is mostly self-regulated by industry though it is sometimes restricted through provincial school policies. The purpose of this study was to document the type of food marketing activities occurring in Canadian schools and examine differences by school characteristics. Methods An online survey was sent to public primary and secondary schools from 27 school boards in Ontario, British Columbia, and Nova Scotia and was completed by 154 Principals in spring 2016. This survey queried the type of food marketing occurring in schools including advertisements, food product displays, fundraising, exclusive marketing agreements, and incentive programs, among others. The occurrence of food marketing was described using frequencies, medians, and ranges. Chi-square and Fisher Exact tests were conducted to assess school-level differences in the frequency of marketing activities by school type (primary versus secondary), province (Ontario versus British Columbia), and the socio-economic status of most students (low versus middle/high income). The significance level was set at α < 0.05 for all tests. Results Overall, 84% of schools reported at least one type of food marketing and the median number of distinct types of marketing per school was 1 (range 0–6). The most frequently reported forms of marketing were the sale of branded food, particularly chocolate, pizza, and other fast food, for fundraising (64% of schools); food advertisements on school property (26%), and participation in incentive programs (18%). Primary schools (n = 108) were more likely to report participating in incentive programs (25%) and selling branded food items (72%) compared to secondary schools (n = 46; 2 and 43% respectively; p < 0.01). Conversely, secondary schools were more likely to report food advertising on school property (56%), exclusive marketing arrangements with food companies (43%), and food product displays (19%) than primary schools (13, 5 and 2%, respectively; p < 0.01). Conclusion The presence of food marketing in most participating schools suggests that the current patchwork of policies that restrict food marketing in Canadian schools is inadequate. Comprehensive restrictions should be mandated by government in both primary and secondary schools to protect children and youth from this marketing.